Activity standardization, photon emission probabilities and half-life measurements of 177Lu. (March 2016) - Dryák, Pavel; Sochorová, Jana; Šolc, Jaroslav; Auerbach, Pavel
Abstract: Activity standardization of 177 Lu and measurement of two nuclear parameters were done. Activity standardization of 177 Lu was done utilizing the 4πβ–γ coincidence method with a combined standard uncertainty of 0.28%. Emission probability of 112.95 keV and 208.37 keV was measured by calibrated spectrometer with HPGe detector. The efficiency was computed with MCNP code and validated using experimental points. Half-life was derived from prolonged measurement of peak area by three different spectrometer systems and also from measurement with ionization chamber. Highlights: Absolute activity measurement of radionuclide 177 Lu. Yield of photons measurement. Half-life measurement.